2010
DOI: 10.1155/2010/731426
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Renal Function at 6 Months with Tacrolimus Combined with Fixed-Dose Sirolimus or MMF: Results of a Randomized Multicenter Trial in Renal Transplantation

Abstract: In a multicenter trial, renal transplant recipients were randomized to tacrolimus with fixed-dose sirolimus (Tac/SRL, N = 318) or tacrolimus with MMF (Tac/MMF, N = 316). Targeted tacrolimus trough levels were lower in the Tac/SRL group after day 14. The primary endpoint was renal function at 6 months using creatinine clearance (Cockcroft-Gault) and was comparable at 66.4 mL/min (SE 1.4) with Tac/SRL and at 65.2mL/min (SE 1.3) with Tac/MMF (completers). Biopsy-confirmed acute rejection was 15.1% (Tac/SRL) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Results from recent studies, however, have suggested that de novo CNI-free immunosuppression with an mTORi may incur an increased risk of acute rejection (6)(7)(8) and adverse events (9), such that complete CNI avoidance is not generally considered advisable (10). Instead, attention has focused on employing mTORi to achieve low-exposure CNI regimens (11)(12)(13)(14)(15)(16) or to facilitate CNI elimination after the initial high-risk period posttransplant (17)(18)(19)(20)(21)(22). Continuing therapy with low-exposure CNI in the presence of an mTORi, while offering effective immunosuppression, has not shown a convincing benefit in terms of renal function when initiated either at the time of transplant (6,(11)(12)(13)15) or subsequently (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from recent studies, however, have suggested that de novo CNI-free immunosuppression with an mTORi may incur an increased risk of acute rejection (6)(7)(8) and adverse events (9), such that complete CNI avoidance is not generally considered advisable (10). Instead, attention has focused on employing mTORi to achieve low-exposure CNI regimens (11)(12)(13)(14)(15)(16) or to facilitate CNI elimination after the initial high-risk period posttransplant (17)(18)(19)(20)(21)(22). Continuing therapy with low-exposure CNI in the presence of an mTORi, while offering effective immunosuppression, has not shown a convincing benefit in terms of renal function when initiated either at the time of transplant (6,(11)(12)(13)15) or subsequently (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, attention has focused on employing mTORi to achieve low-exposure CNI regimens (11)(12)(13)(14)(15)(16) or to facilitate CNI elimination after the initial high-risk period posttransplant (17)(18)(19)(20)(21)(22). Continuing therapy with low-exposure CNI in the presence of an mTORi, while offering effective immunosuppression, has not shown a convincing benefit in terms of renal function when initiated either at the time of transplant (6,(11)(12)(13)15) or subsequently (23,24). Elimination of CNI after the period of highest immunological risk, but before development of extensive CNI-related irreversible tubulointerstitial damage (2), may be a more promising strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty‐one RCTs evaluated sirolimus whereas six RCTs evaluated everolimus. For the primary quantitative analysis, a total of 28 RCTs were published on kidney transplantation reporting on 8916 patients (Tables 1 and 2, Table S1), [13–43] four RCTs were published on heart transplantation reporting on 1289 patients (Table S2), [44–47] one RCT [48] was published on liver transplantation reporting on 78 patients (Table S3) and one RCT [49] was published on simultaneous kidney and pancreas transplantation reporting on 123 patients (Table S4). In kidney transplantation, 14 RCTs evaluated mTOR inhibitors together with CNIs, 13 RCTs evaluated mTOR inhibitors together with antimetabolites and 1 RCT evaluated an mTOR inhibitor together with belatacept.…”
Section: Resultsmentioning
confidence: 99%
“…Renal function at 6 months of follow-up was comparable; however, the study was limited by short followup (27). The Edmonton protocol for islet cell transplantation consists of Tac/SRL maintenance and has been associated with nephrotoxicity (28).…”
Section: Discussionmentioning
confidence: 96%